The tough 1940s for the 1939 Republican Exile - de Hoyos Puente, Jorge (Historia y Memoria de la Educación, 2019)
This paper highlights the main difficulties faced by the Spanish political organizations in exile in the 1940s. Throughout this period, political parties and trade unions had to deal with the Republican defeat and the unlikely perspective of a short-term return. The integration process in the host countries and the possibilities for of a short-term return to Spain were highly conditioned by the internal and external stress to which the Republican exile was subject. In order to understand this process properly, this article focuses on the evolution of the political exile as a whole, addressing the principal conflicts that arose during this key period of its historical transformation. The main premise of the article centers on the broad variety of criteria within the organizations regarding the configuration of a common and unified response to Francoism., This division only weakened any option of achieving an effective combative action against the dictatorship. In addition to analyzing the divergent criteria of the exiles we will also focus on the international factors that affected the anti-Francoist cause during the 1940s.